Angiogenic and inflammatory biomarkers in acute ischemic stroke: The prognostic role of vascular endothelial growth factor, neutrophil-to-lymphocyte ratio, and lymphocyte-to-monocyte ratio in a cross-sectional study - Amran, Muhammad Yunus; Norwanto, Dwi Atmaji; Akbar, Muhammad; Bintang, Andi Kurnia; Massi, Muhammad Nasrum; Atiah, Ummu (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: Acute ischemic stroke (AIS) is a leading cause of morbidity and mortality, with a complex pathophysiological mechanism involving inflammation and angiogenesis. Vascular Endothelial Growth Factor (VEGF), neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and lymphocyte-to-monocyte ratio (LMR) are thought to play roles in determining stroke severity.Methods: This was an observational analytic study with a cross-sectional design conducted on AIS patients at Dr. Wahidin Sudirohusodo General Hospital, Makassar. Serum VEGF levels were measured using the ELISA method, while NLR, PLR, and LMR were calculated from routine blood tests. Stroke severity was assessed using the National Institutes of Health Stroke Scale (NIHSS) and categorized into two groups: moderate (0–15) and moderate-to-severe (16–42). Pearson correlation and linear regression analyses were performed to evaluate the relationships between variables.Results: A total of 50 patients met the inclusion criteria (54% male, 46% female). Correlation analysis showed a significant positive association between VEGF and NIHSS (r = 0.831; p = 0.000), as well as between NLR and NIHSS (r = 0.548; p = 0.000). LMR demonstrated a significant negative correlation with NIHSS (r = −0.549; p = 0.000). In contrast, PLR was not significantly associated with NIHSS (r = 0.228; p = 0.112). Multiple regression analysis identified VEGF and NLR as dominant predictors (R² = 0.735; p < 0.001).Conclusions: Serum VEGF, NLR, and LMR were significantly associated with the severity of AIS, whereas PLR was not. VEGF and NLR may be considered potential biomarkers for risk stratification in AIS patients.